STRATEGI GURU MELALUI PENDIDIKAN TA’DIB DALAM PEMBINAAN AKHLAK SISWA - NAZARUDDIN NAZARUDDIN (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
Education is assistance provided by adults who are responsible for students to reach the level of maturity, both physically and mentally. Education is a very important thing for humans in living their lives in the world to get to the hereafter. With education, a person can manage his life in accordance with the divine provisions that have been arranged in Islamic teachings. The first education obtained is from the family environment, then schools are assisted by teachers and the community and environment.